2021
DOI: 10.1128/jvi.00672-21
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of JIP4 at S730 Presents Antiviral Properties against Influenza A Virus Infection

Abstract: Influenza A virus (IAV) is the causative agent of flu disease that results in annual epidemics and occasional pandemics. IAV alters several signaling pathways of the cellular host response in order to promote its replication. Therefore, some of these pathways can serve as targets for novel anti-viral agents. Here, we show that c-Jun NH2-terminal kinase (JNK)-interacting protein (JIP) 4 is dynamically phosphorylated in IAV infection. Lack of JIP4 resulted in higher virus titers with significant differences in v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…SPAG9 has been reported to affect the replication of IAV ( 20 ). Therefore, to exclude the possibility that different cell death rates may be caused by distinct viral replication levels, a high multiplicity of infection (MOI) of 2 was used to maximize cell death independent of differences in viral replication.…”
Section: Resultsmentioning
confidence: 99%
“…SPAG9 has been reported to affect the replication of IAV ( 20 ). Therefore, to exclude the possibility that different cell death rates may be caused by distinct viral replication levels, a high multiplicity of infection (MOI) of 2 was used to maximize cell death independent of differences in viral replication.…”
Section: Resultsmentioning
confidence: 99%
“…Among JIP proteins, SPAG9 or JIP4 (also known as MAPK8IP4) is involved in MAPK signaling pathway to regulate cellular activities 71 . Del Sarto et al recently have identified an increase of phosphorylaton at Ser730 in JIP4 after Influenza A virus infection 72 . Similarly, other work has recently described that this phosphorylation promotes cell death via c-jun kinase signaling pathway 73 .…”
Section: Discussionmentioning
confidence: 96%
“…after Influenza A virus infection 72 . Similarly, other work has recently described that this phosphorylation promotes cell death via c-jun kinase signaling pathway 73 .…”
Section: Del Sarto Et Al Recently Have Identified An Increase Of Phos...mentioning
confidence: 99%
“…Among JIP proteins, SPAG9 or JIP4 (also known as MAPK8IP4) is involved in MAPK signaling pathway to regulate cellular activities (79). Del Sarto et al recently have identified an increase of phosphorylaton at Ser730 in JIP4 after Influenza A virus infection (80). Similarly, other work has recently described that this phosphorylation promotes cell death via c-jun kinase signaling pathway (81).…”
Section: Discussionmentioning
confidence: 98%
“…Del Sarto et al. recently have identified an increase of phosphorylaton at Ser730 in JIP4 after Influenza A virus infection ( 80 ). Similarly, other work has recently described that this phosphorylation promotes cell death via c-jun kinase signaling pathway ( 81 ).…”
Section: Discussionmentioning
confidence: 99%